The role of oxidative stress on cardiovascular disease in metabolic syndrome: Efficacy and safety of EGCG and CGA - Nugroho, Ira Vori; Rohman, Mohammad Saifur (Universitas Brawijaya, 2026)
The challenge of cardiovascular disease has spread across the globe, especially concerning metabolic syndrome and its components. There is a need to look for new treatment strategies that attack underlying pathophysiological mechanisms. This review discusses the role of oxidative stress in the development and progression of cardiovascular complications in metabolic syndrome while evaluating the therapeutic potential of two natural compounds as antioxidants: epigallocatechin gallate (EGCG) from green tea and chlorogenic acid (CGA) from coffee. Oxidative stress disrupts normal cellular function through multiple pathways, including LDL oxidation, nitric oxide function, glycolysis, modified TCA cycle activity, and activation of inflammatory cascades. These mechanisms contribute to CVD's endothelial dysfunction, atherosclerosis, and cardiac remodelling. Despite its limited bioavailability and concentration-dependent effects, EGCG demonstrates significant cardiovascular benefits through enhanced NO bioavailability, activation of antioxidant pathways, and suppression of inflammatory responses. CGA shows promising results in hypertension management and endothelial function improvement, with clinical studies reporting significant blood pressure reductions and improved vascular function. These natural compounds could serve as valuable add-on therapeutic agents for treating cardiovascular disease associated with metabolic syndrome. However, optimal dosing strategies and individual patient factors require further investigation